Brand Image Impression on Customer Satisfaction Aston Gorontalo Hotel & Villas - Bening , Ghina Gerimis; Karundeng, Deby R.; Suyanto , Moh. Afan (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This study aims to obtain impressionsBrand Image For ASTON Gorontalo Hotel & Villas Customer Satisfaction which includesBrand Identity, Brand Personality, Brand Association, Brand Benefit and Competence, Brand Attitude and Behavior. The research method used in this research is descriptive qualitative. Data collection techniques using interviews, observation and documentation studies. The research results show that Fourth variabel is Brand Identity, Brand Personality, Brand Identity, Brand Personality effect on customer satisfaction whereasBrand Association does not significantly affect customer satisfaction. Customer Satisfaction Obtained of service especially for friendly employees. Customers also recommend ASTON Gorontalo for a place to stay in Gorontalo.